Clinical Holistic Medicine: When Biomedicine is Inadequate - Søren Ventegodt; Mohammed Morad; Eytan Hyam; Joav Merrick (The Scientific World Journal)
The modern physician is using pharmaceuticals as his prime tool. Unfortunately, this tool is much less efficient than you might expect from the biochemical theory. The belief in drugs as the solution to the health problems of mankind, overlooking important existing knowledge on quality of life, personal development, and holistic healing seems to be one good reason why approximately every second citizen of our modern society is chronically ill. The biomedical paradigm and the drugs are certainly useful, because in many situations we could not do without the drugs (like antibiotics), but curing infections or diseases in young age is not without consequences, as the way we perceive health and medicine is influenced by such experiences. When we get a more severe disease in midlife, we also believe drugs will make us healthy again. But at this age, the drugs do not work efficiently anymore, because we have turned older and lost much of the biological coherence that made us heal easily when we were younger. Now we need to assume responsibility, take learning, and improve our quality of life. We need a more holistic medicine that can help us back to life by allowing us to access our hidden resources. The modern physician cannot rely solely on drugs, but must also have holistic tools in his medical toolbox. This is the only way we can improve the general health of our populations. Whenever NNT (Number Needed to Treat) is 2 or higher, the likelihood of the drug to cure the patient is less than 50%, which is not satisfying to any physician. In this case, he must ethically try something more in order to cure his patients, which is the crossroads where both traditional manual medicine and the tools of a scientific holistic medicine are helpful.